'We Care', and 'They Need Help': The Disabled in the Print Media. - Don, Zuraidah Mohd; Ang Pei Soo (Pertanika Journal of Social Sciences & Humanities, 2014)
In this paper, we examine the way a leading Malaysian newspaper represents the act of charitable giving on the part of big corporate organisations that take on the role of benefactor in order to fulfil their corporate social responsibilities. Drawing on the methodology of critical discourse analysis, we examine extracts from four newspaper reports selected from a corpus of 179 texts. The aim of the analysis is to find out how the news reports represent the charitable act (i.e. the donation), the organisation performing the act (i.e. the benefactor), and the object of the act (i.e. the recipient) in its report of the charitable event. This question is critical because the answer reveals the unequal distribution of power in the relationship constructed between benefactor and recipient. We also set out to discover how the different voices are incorporated into the writer's voice. The analysis reveals in addition the manner in which the discourse of charitable giving becomes inextricably entwined with the discourse of advertising and promotion.